Voices of experience : narratives of mental health survivors - Basset, Thurstine; Stickley, Theo.; Wiley InterScience (Online service) (Chichester : Wiley-Blackwell, 2010)
Voices of Experience contains a wide range of stories written by mental health survivors. The narratives illustrate how survivors have developed self-management techniques and strategies for living which, together, offer a guide to anybody struggling with 21 st century life.: Explores a wide variety of mental distress experiences, underpinned by many different explanations and beliefs; Narrative has been central to the recovery approach and this book presents stories of recovery as well as an appraisal of the concept; Challenges simplistic explanations of recovery and offers a critical angle t.
The antidote to madness : crystallising out the real self / Peter Chadwick -- Poem : but what is the cause? / Libby Jackson -- Surviving the system / Peter Campbell -- Poem : they come and go / Dave St. Clair -- Poem : fixing dinner / Dave St. Clair -- Measuring the marigolds / Alison Faulkner -- Poem : the tears I cry / Mariyam Maule -- Coping strategies and fighting stigma / Joy Pope -- Poem : day by day / Libby Jackson -- Living with the dragon : the long road to self-management of bi-polar II / Peter Amsel -- Poem : in exile / Mariyam Maule -- Coping strategies / Ruth Dee -- Poem : puppeteer / Esta Smith -- What's it like having a nervous breakdown? : can you recover? / Laura Lea -- Poem : a journey beyond silence / Mariyam Maule -- The bridge of sighs and the bridge of love : a personal pilgrimage / Peter Gilbert -- Poem : have you ever felt lonely? / Dave St. Clair -- Poem : he saved my bacon / Dave St. Clair -- The holy spirit : healer, advocate, guide, and friend / Richard Lilly -- Poem : mist of tears / Brice Jones -- Capital writings / Thomas France [and others] -- Poems : nicely nicely nought / Martin Snape -- Feel easy-fit / Martin Snape -- The value of self-help/peer support / Sarah Collis, Caroline Bell, and Joan Cook -- Poem : the clear sky / Dave St. Clair -- A recovery approach in mental health services : transformation, tokenism or tyranny? / Premila Trivedi -- Poem : to what could have been / Mariyam Maule --. Stand to reason / Jonathan Naess -- Poem : I am / Libby Jackson -- Walking with dinosaurs / John Stuart Clark -- Poem : negatives and positives / Libby Jackson -- Poem : the heart of humankind / Mariyam Maule.
Includes bibliographical references and index.
Print version record.
Keywords: Mentally ill -- Biography; Mentally Ill Persons; Adaptation, Psychological; Mental disorders; Survivors; Medicine; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; Mentally ill; Autobiography; Electronic books; Biography